Influencia de la disfemia en el aprovechamiento escolar de los niños/as de educación básica de la unidad educativa Teodoro Alvarado Garaicoa, cantón Alfredo Baquerizo Moreno, Provincia del Guayas. - Ube del Rosario, Viviana Mercedes (2016)
With this paper is to analyze the reason why there are children with stuttering, how can you understand stuttering and, ultimately, what is the disfemia. For this purpose the most recent data from molecular genetics, cognitive science and evolutionary psychology are analyzed. Based on the family doctor can diagnose, and possibly provide medical treatment, counseling and information to parents about the characteristics of this disease. This paper addresses the issue of stuttering has been prepared taking into account my concern as a primary care physician and suffering this